Features of inflation and methods of minimization of inflationary tendencies in Russia - O. V. Shatayeva; O. T. Shipkova; V. A. Nikityuk (Путеводитель предпринимателя, 2020)
The Article touches one of the most important indicators ofthe development of the economy - inflation, inflation rate and compares the effectiveness of economic policy of the State to the stability ofthe economic system of the country and other countries. Considered the beginning of the 1990s to the present. The authors analyzed the causes ofthe inflation processes, consequences and ways out ofit. Considered public policy inflationary and how all this affects the standard of living in the country.